THE ANTHELMINTIC EFFECTS OF ETHANOL EXTRACT OF CURANGA FEL-TERRAE LEAVES ON ASCARIDIA GALLI - Patilaya, Popi; Husori, Dadang Irfan; Sumantri, Imam Bagus (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: This study was to investigate the anthelmintic effects of ethanol extract of Curanga fel-terrae leaves on Ascaridia galli. Methods: Extract of C. fel-terrae was prepared by percolating the dried powder of the plant leaves. To observe anthelmintic effects, A. galli was exposed to the plant extract solutions in different concentrations at room temperature for 72 hrs. Sodium chloride 0.9%, sodium carboxymethyl cellulose 0.5%, and albendazole 0.1% were served as negative control, solvent control, and positive control, respectively. The anthelmintic effects were determined by observing the time taken for paralysis and the time taken for death of A. galli during experiment. Results: The results demonstrated that there were no different effects between negative and solvent controls. However, the ethanol extract of C. fel-terrae leaves exhibited significantly paralysis and death effects toward A. galli. The plant extracts at the concentration of 100 mg/ml showed similar anthelmintic effects with albendazole 0.1%. This study also indicated that the paralysis and death effects of plant extract were shorter when the worms exposed with the concentration above of 100 mg/ml. Conclusion: This study indicated that the ethanol extract of C. fel-terrae leaves has potential anthelmintic effects on A. galli. Keywords: Curanga fel-terrae, Ascaridia galli, Anthelmintic, Helminthiasis, Ascariasis. Â 